Treatment of Spitz nevus and spitzoid lesions in children. - Coppola, V.; Di Mento, C.; Cerulo, M.; Esposito, G.; Fornaro, L.; Scalvenzi, M.; Escolino, M.; Ciro, E. (European Journal of Pediatric Dermatology, 2025)
Purpose. Spitzoid lesions are classified into Spitz nevi, Spitz tumors, and spitzoid melanomas. While the understanding of Spitz nevi has improved, the malignant potential of Spitz tumors remains uncertain, leading to diagnostic and management challenges. This study evaluates the surgical management of pediatric patients with suspected Spitz lesions. Methods. Fifty-eight pediatric cases of suspected Spitz lesions were analyzed. Demographics, lesion characteristics, surgical indications, histopathology, and follow-up were collected. Histopathologic groups included Spitz nevus (G1), Spitz nevus/tumor with mild atypia (G2), Spitz tumor with moderate atypia (G3), and spitzoid melanoma (G4). Subgroups were based on the need for additional procedures (A) or follow-up only (B). Results. The mean age of the patients was 14.6 years, with a female predominance (58%). The lesions were commonly located on the limbs (51%), chest (35%), and head (9%). Histopathological findings included: 37 (64%) Spitz nevi (G1), 9 (15%) Spitz nevi/tumor (G2), 11 (19%) Spitz tumors (G3), and 1 case of spitzoid melanoma (G4). Additional procedures were required in 5/9 (55%) in G2, 10/11 (91%) in G3, and 1/1 in G4, mostly involving margin widening. In all G2 cases (5/5) and most G3 cases (8/10), margin widening was unnecessary. Conclusion. The diagnosis of suspected Spitz tumors in children often lacks clarity, leading to treatment decisions influenced by the physicians’ experience rather than by standardized guidelines. Margin widening should be limited to cases with high-grade atypical Spitz tumors. In addition, other factors, such as cosmetic considerations and potential complications, especially in visible areas, should always be taken into account.